Harnessing Emotional Intelligence: Enhancing Employee Performance in Kerala’s Retail Textile Industry - Simson, C. S.; Kinslin, D. (Indian Journal of Information Sources and Services, 2024)
This research explores the effects of EI (Emotional Intelligence) on employee performance in the retail textile industry in Kerala with specific reference to the moderating roles of organizational culture and leadership style. With the ever-growing demands of the retail sector, it is imperative to demonstrate the efficiency of EI in improving employee performance to support a sustained competitive advantage. This research adopts a descriptive research design, whereby both quantitative and qualitative data will be collected to capture the goals and objectives of the study. Structural equation Modelling (SEM) was used to determine the relationship between EI and the level of performance of employees, as well as the moderating role of organizational culture and leadership style. This study focuses on textile manufacturing employees of the selected retail outlets of Kerala, with a sample size of 250. The results are expected to help explain how EI can enhance performance, especially under conditions of leadership support and organizational culture. The implications of these findings should offer explicit counsel to managers in the retail textile industry to facilitate a work climate that boosts the emotional capabilities of workers, resulting in increased work efficiency and contentment. Apart from extending the body of knowledge on emotional intelligence and employee performance, the findings of this study provide an important guideline for the retail sector of Kerala with regard to emotional intelligence that must be developed to enhance performance and sustain business success in the future.